Implementasi Pendidikan Karakter Melalui Mata Pelajaran Agama Buddha Pada Siswa Kelas IX SMB Vimala Maitreya Pancur Jaya - Anen Anen (Jurnal Maitreyawira, 2024)
This study aims to describe the implementation of character education learning at SMB Vimala Maitreya Pancur Jaya. Classroom Action Research Model (CAR) as a class IX student respondent as many as 30 students. The results of research with procedures for planning, implementing, observing, and reflecting. It has been well implemented, as shown by the results of learning and character understanding, the average value of students shows an increase in understanding from 70 in the pre-cycle to 76 in cycle I, increasing to 82 in cycle II until all students have completed (≥70 KKM) ) in receiving character-based Buddhism lessons, in terms of percentage there was an increase in understanding of 30% in cycle I and 17% in cycle II to 100%. This shows that the understanding of character education is successfully understood by students, Buddhist teachers more actively involve students in character lessons with group discussions on themes such as religion, honesty, discipline, and courtesy.